2014
DOI: 10.1007/s11938-014-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gastroparesis: Beyond Basics

Abstract: Gastroparesis is defined as the presence of delayed gastric emptying in the absence of mechanical obstruction, with a variety of upper gastrointestinal symptoms. Although measurement of gastric emptying is necessary for the diagnostic labeling, this finding has little impact in terms of explaining the symptom pattern and determining the prognosis and therapeutic approach. Clinical management is based on ruling out of mechanical causes and serum electrolyte imbalances, followed by initial medical treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In the late stage of diabetes, plasma ghrelin is decreased, which might be associated with anorexia, muscle atrophy, decreased body mass, or even gastric paralysis. Clinical studies have shown that patients with DGP have decreased serum ghrelin content [22]. The results in our study suggested that the content of serum ghrelin in the model group was lower than that in the blank group; our results are consistent with the previous literature.…”
Section: Study On the Influence Of Acupoints Selection On Ghrelin Andsupporting
confidence: 92%
“…In the late stage of diabetes, plasma ghrelin is decreased, which might be associated with anorexia, muscle atrophy, decreased body mass, or even gastric paralysis. Clinical studies have shown that patients with DGP have decreased serum ghrelin content [22]. The results in our study suggested that the content of serum ghrelin in the model group was lower than that in the blank group; our results are consistent with the previous literature.…”
Section: Study On the Influence Of Acupoints Selection On Ghrelin Andsupporting
confidence: 92%
“…5,7,8 Treatment is medical therapy using prokinetics with metoclopramide. 9,10 If refractory to medical therapy, non-pharmacologic treatment, including botulinum toxin injection or gastric electrical stimulation, can be attempted; 10,11 however, this remains to be controversial. 10 Recently, G-POEM has been regarded as an emerging treatment.…”
Section: Diagnosis: Idiopathic Gastroparesismentioning
confidence: 99%
“…However, none to date has reached a developmental stage compatible with becoming a prescription drug [16].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%